Pemetaan Lahan Sub-Optimal Berbasis Nilai NDVI Sentinel 2a: Studi Pendahuluan - Indarto, Indarto; Nadzirah, Rufiani; Reksa Belagama, Hadrian (Universitas Diponegoro, 2020)
Normalised Difference Vegetation Index (NDVI) is one of the vegetation indices used to analyse vegetation density. This study presents the potential use of NDVI to map dry-marginal-agricultural land (Dry-MAL). The study conducted in the eastern part of Situbondo, which includes three districts, namely, Arjasa, Asembagus and Jangkar. Sentinel-2A (recorded in 2018) and 450 Control points (GCPs) are used as the primary input. The region is an area with distinctive climate characteristics, where the dry season is longer than the rainy season. Analysis using